1997
DOI: 10.1038/sj.leu.2400818
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations in atypical chronic lymphocytic leukemia: a cytogenetic and interphase cytogenetic study

Abstract: To define better the chromosomal profile of atypical chronic karyotype may in fact carry chromosomally abnormal clones lymphocytic leukemia (aCLL), cytogenetic and interphase cytoescaping detection at metaphase analysis due to their low genetic studies were performed in 43 cases, using mitogenmitotic index. a relatively poor prognosis may be associated with aCLL.The presence of ؉12, 13q14 deletions, 11q, and 6q21-q23 anomalies in 19 cases was associated with a 2-month median interTo define better the cytogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…57,58 Recent studies examining molecular aberrations, including p53 mutations, unfavorable cytogenetics, CD38 expression, and somatic variable-heavy (VH) gene mutational status, have demonstrated that these are also important determinants for treatment outcome in CLL. [42][43][44][45][46][47][48][49][50][59][60][61][62][63][64][65][66] It is of interest that several standard prognostic factors, including age, Rai stage, and B 2 M level, were not shown to be important in predicting treatment outcome for the group of patients treated in this trial. Similar results with respect to the lack of importance of age to treatment outcome have been observed in the 2 trials examining altered dosing of rituximab therapy in previously treated patients with CLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 Recent studies examining molecular aberrations, including p53 mutations, unfavorable cytogenetics, CD38 expression, and somatic variable-heavy (VH) gene mutational status, have demonstrated that these are also important determinants for treatment outcome in CLL. [42][43][44][45][46][47][48][49][50][59][60][61][62][63][64][65][66] It is of interest that several standard prognostic factors, including age, Rai stage, and B 2 M level, were not shown to be important in predicting treatment outcome for the group of patients treated in this trial. Similar results with respect to the lack of importance of age to treatment outcome have been observed in the 2 trials examining altered dosing of rituximab therapy in previously treated patients with CLL.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Overexpression of several antiapoptotic proteins (mcl-1, bag-1) and the presence of specific genetic aberrations [p53 mutations, ataxia telangiectasia gene mutations, and interphase cytogenetic abnormalities including del(17p13)] have been associated with poor response to fludarabine-based therapy. [42][43][44][45][46][47][48][49][50] One of the attractive features of immunotherapy with monoclonal antibodies, such as rituximab, is that the proposed mechanism of cell clearance is different from that of cytotoxic chemotherapy, involving both complement-mediated cell lysis and antibody-dependent cellular cytotoxicity. [51][52][53] However, recent evidence shows that a portion of CLL patients receiving rituximab treatment have in vivo activation of caspase-9, caspase-3, and poly-adenosine-5Ј-diphosphate-ribose polymerase (PARP) cleavage in blood leukemia cells immediately following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cyclin D1 alterations are tumor-type specific, and occur through chromosomal translocation, gene amplification, or excessive accumulation of the protein. Chromosomal translocation of cyclin D1 is relatively rare in most cancers, but occurs in greater than 90% of Mantle Cell lymphoma, a mature B-cell malignancy (Bosch et al, 1994;De Wolf-Peeters and Pittaluga, 1994;Bigoni et al, 1996). This same translocation (11;14)(q13;q32) is also observed at a lower frequency mutliple myeloma and specific leukemias (Bosch et al, 1994;Bergsagel and Kuehl, 2005).…”
Section: Cyclin D1 Alterations In Cancermentioning
confidence: 99%
“…Deletion of the 13q14 region occurs in more than half of the cases of B cell chronic lymphocytic leukemias and also in 50 % of mantle cell lymphomas, in 16-40 % of multiple myelomas and in 60 % of prostate cancers, suggesting that tumor suppressor(s) gene(s) at 13q14 are involved in the pathogenesis of these tumors 64,65,66,67 . Calin et al (2002) have shown that two miRNA genes are located at 13q14.3 within a 30-kb region of minimal loss in CLL between two exons of the LEU2 gene.…”
Section: Hematological Malignanciesmentioning
confidence: 99%